Del objeto prodigioso al prestigio literario - Fermín Gil Encabo (Mélanges de la Casa de Velázquez)
In 17th-century Spain, Huesca was the site of a cultural experiment rooted in patronage, political interests connected with “neoforalism”, and pre-scientific experimentalism. At its centre, Lastanosa provides an illustration of the manifestation of power by association with the prestige of objects. The economic, intellectual and environmental traits of his collections throw light on a system of acquisition and exchange of rare and valuable objects from all over the world based on a network of contacts, foremost among whom were noble antiquarians, jurists, historians and Jesuit scientists.  It was a paradox of collectorship that treasures needed to be displayed at public festivals and shown to those visiting the collector’s palace. The same can be said of the sources of information (some of which have proven false), perhaps the most notable of which is the description by Gracián in which the wonders of Lastanosa’s collections are immortalised without reference to their material aspects.